Impaired dacarbazine activation and 7-ethoxyresorufin deethylation in vitro by polymorphic variants of CYP1A1 and CYP1A2: implications for cancer therapy. Issue 10 (October 2016) - Lewis, Benjamin C.; Korprasertthaworn, Porntipa; Miners, John O.
Abstract : Objectives: To extend our understanding of how interindividual variability mediates the efficacy of cancer treatment. Materials and methods: The kinetics of dacarbazine (DTIC) N -demethylation by the most frequent polymorphic variants of CYP1A1 (T461N, I462V) and CYP1A2 (F186L, D348N, I386F, R431W, R456H) were characterized, along with kinetic parameters for the O -deethylation of the prototypic CYP1A substrate 7-ethoxyresorufin, using recombinant protein expression and high-performance liquid chromatographic techniques. Results: A reduction of ∼30% in the catalytic efficiencies (measured as in-vitro intrinsic clearance, CLint ) was observed for DTIC N -demethylation by the two CYP1A1 variants relative to wild type. Although a modest increase in the CLint value for DTIC N -demethylation was observed for the CYP1A2 D348N variant relative to the wild type, the CLint for the F186L variant was reduced and the I386F, R431W, and R456H variants all showed loss of catalytic function. Conclusion: Comparison of the kinetic data for DTIC N -demethylation and 7-ethoxyresorufin O -deethylation indicated that alterations in the kinetic parameters ( K m, V max, CLint ) observed with each of the CYP1A1 and CYP1A2 polymorphic variants were substrate dependent. These data indicate that cancer patients treated with DTIC who possess any of the CYP1A1-T461N and I462V variants or the CYP1A2-F186L, D348N, I386F, R431W, and R456H variants are likely to have decreased prodrug activation, and hence may respond less favorably to DTIC treatment compared with individuals with wild-type CYP1A alleles.